IMPLIKASI UJI KOMPETENSI TERHADAP KESADARAN HUKUM PERS WARTAWAN MEDIA CETAK DI KOTA DENPASAR - Adnyana, I Made (Jurnal Magister Hukum Udayana (Udayana Master Law Journal); Vol 4 No 2 (2015)DO - 10.24843/JMHU.2015.v04.i02.p02, 2015)
This research aim to analyze how far the competency test implication on press legal awareness of print journalists in Denpasar. The research method used is sociology approach on print journalists in Denpasar that pass competency test. To collect data from print journalists in Denpasar on how the implication of competency test affect press legal awareness, method of law as it is in society is used with quantified non-doctrinal approach. Based on the press laws in Indonesia, there no rules that sternly or specifically made regarding competency test. The competency test conducted base on Regulation of Press Council No. 1 of 2010 about Journalists Competency Standard. The enactment of regulation is part of function implementation of Press Council according to Article 15 of Law No. 40 of 1999 on the Press journalists . Press legal awareness of print journalists in Denpasar basically affected by own awareness to know and learn about press legal regulations and opportunity that given by print media company to attend training on law and ethic, both internal or external, and taking competency test. In conclusion, competency test has implication on the press legal awareness of print journalists.
Keywords: Competency Test Implication, Legal Awareness, Law Press, Journalist